Assur Group Number Synthesis of Multi-loop with Multiple Joints - Sun Liangbo; Kong Jianyi; Xiao Qu (Jixie chuandong)
The results of Assur group model synthesis and number synthesis are briefly discussed,a combination of kinematic chain characteristic value is used to marker the result of number synthesis. Based on the analysis of kinematic chain characteristic value expression,the data rang of mutiple components or multiple joints,binary component and the key points and so on are analyzed and discussed. On the basis of above analysis,the number synthesis method of planar kinematic chain is proposed based on the dichotomy. With high computing efficiency,all the number synthesis results for 4 10 components with multiple joints are obtained,and then some samples are listed to analyze the effectiveness of the number synthesis results. The necessary information for the digital kinematic chain type integrated is provided by the above results.